POWER & Choice AN INTRODUCTION TO POLITICAL SCIENCE - Shively, W. Phillips 1942-; Schultz, David (Rowman & Littlefield, 2022)
Power & Choice offers an in-depth look into the nuances of politics through the analysis of collective choices for a group or state through the use of power. Using extended case examples from around the world, Power & Choice provides undergraduate students with a clear and engaging introduction to political science and comparative politics.